The missing link - om vandrebevægelse og mangel på samme i Danmark - Haahr, Jakob (Forum for Idræt, 2010)
I artiklen sættes med afsæt i fjernvandreruten fokus på, hvad det er der gør, at vi i Danmark ikke har samme vandrekultur som i vores nabolande. The Missing Link A long-distance footpath runs from Kilpisjärvi in northern Finland to Alexandroupolis in Greece. However the track does not cross intact but is interrupted on the island of Funen in Denmark. It is no coincidence that the rupture is in Denmark, nor that it is on Funen. In this article this ‘missing link’ provides the starting point to discuss a walking culture, which in Denmark is notable by its absence. At the beginning of 20th century, thanks to the influence of neighbouring countries, the culture of walking did increasingly make itself felt in Denmark. Longer walks became popular and many Danes embarked on hiking tours, walking for several days and spending the night at special ‘vandrehjem’ (or ‘youth hostels’). Since the Second World War this culture has more or less disappeared, and the question asked here is why? The article is divided in two parts. In the first there is a historical review of the development of the Danish culture of walking from the beginning of 20th century until the late 1930’s. This is followed by a discussion of the circumstances that led to the disappearance of this walking culture, focusing on the long distance footpath. This centres on a jostling for supremacy among sporting factions and on the struggle between various outdoor interests, between different management concerns, and between farmers, the state and local authorities about who should have the right to develop and exploit the landscape in southern Funen area. In this struggle organisations representing outdoor activities have been poorly organized and until now the landscape has primary been developed on the premises of agriculture, industry and urbanism. Today the position and status of outdoor life (friluftsliv) and the culture of hiking are improving. Councils in particular are focusing on health, tourism and attracting new residents´, and there is both a political and a popular will to establish hiking trails. For the long-distance footpath these changes mean that the missing link on Funen now disappears and that the hiking trail across Europe is established.